Biphasic silica/apatite co-mineralized collagen scaffolds stimulate osteogenesis and inhibit RANKL-mediated osteoclastogenesis. (June 2015) - Jiao, Kai; Niu, Li-na; Li, Qi-hong; Chen, Fa-ming; Zhao, Wei; Li, Jun-jie; Chen, Ji-hua; Cutler, Christopher W.; Pashley, David H.; Tay, Franklin R.
Graphical abstract: Abstract: The effects of a biphasic mineralized collagen scaffold (BCS) containing intrafibrillar silica and apatite on osteogenesis of mouse mesenchymal stem cells (mMSCs) and inhibition of receptor activator of nuclear factor κB ligand (RANKL)-mediated osteoclastogenesis were investigated in the present study. mMSCs were cultured by exposing to BCS for 7 days for cell proliferation/viability examination, and stimulated to differentiate in osteogenic medium for 7–21 days for evaluation of alkaline phosphatase activity, secretion of osteogenic deposits and expression of osteoblast lineage-specific phenotypic markers. The effect of BCS-conditioned mMSCs on osteoclastogenesis of RAW 264.7 cells was evaluated by tartrate-resistant acid phosphatase staining and resorption pit analysis. The contributions of mitogen-activated protein kinase (MAPK) and phosphatidylinositol-3 kinase (PI3K) signal transduction pathways to osteogenesis of mMSCs and their osteoprotegerin (OPG) and RANKL expressions were also evaluated. Compared with unmineralized, intrafibrillarly-silicified or intrafibrillarly-calcified collagen scaffolds, BCS enhanced osteogenic differentiation of mMSCs by activation of the extracellular signal regulated kinases (ERK)/MAPK and p38/MAPK signaling pathways. After mMSCs were exposed to BCS, they up-regulated OPG expression and down-regulated RANKL expression through activation of the p38/MAPK and PI3K/protein kinase B (Akt) pathways, resulting in inhibition of the differentiation of RAW 264.7 cells into multinucleated osteoclasts and reduction in osteoclast function. These observations collectively suggest that BCS has the potential to be used in bone tissue engineering when the demand for anabolic activities is higher than catabolic metabolism during the initial stage of wound rehabilitation.